THE IMPLEMENTATION OF LISTEN READ DISCUSS STRATEGY TO TEACH READING OF RECOUNT TEXT. - NUGROHO, DICKY CAHYO (RETAIN, 2021)
Abstract This research aims to examine the implementation of the LRD (Listen-Read-Discuss) strategy to teach reading of recount text and to discover the obstacles faced by the teachers and the students during teaching learning reading of recount text using LRD strategy. This research uses theory of reading and theory of LRD by Manzo and Casale. This research is descriptive qualitative. The subjects of this research are two English teachers and X grade students of MA Amanatul Ummah Mojokerto. To obtain the data, the researcher uses observation, interview, and questionnaire. The data were analyzed inductively, qualitatively, and interpretively. The results of this research show that the implementation of LRD strategy to teach reading of recount text is still less successful, less effective, and not maximal. The problems that arise in this study can be seen from the point of view of the teacher, the teacher has difficulty managing the time in implementing the LRD steps, while from the student's point of view, the lack of vocabulary is the reason this strategy does not work optimally. Keywords: LRD strategy, Teaching Reading, Recount text.